Identification of basic helix-loop-helix transcription factors reveals candidate genes involved in pathogenicity of Fusarium pseudograminearum. Issue 2 (3rd April 2019) - Chen, Linlin; Geng, Xuejing; Ma, Yuming; Zhao, Jingya; Li, Tianli; Ding, Shengli; Shi, Yan; Li, Honglian
Abstract: The basic helix-loop-helix (bHLH) transcriptional regulatory proteins are key players in a wide array of developmental processes and abiotic stress responses. The bHLH domain has been identified and functionally characterized from fungi to humans. However, no systematic characterization of a bHLH family has been reported in Fusarium pseudograminearum . Fusarium pseudograminearum is an important plant pathogen that causes crown rot of wheat and barley. In this study, 17 FpbHLH genes with conserved residues in the bHLH domain were identified using a whole-genome searching approach. In addition, transcription profiling results showed that 11 FpbHLH genes were responsive to infection – eight of them ( FpbHLH2, FpbHLH6, FpbHLH7, FpbHLH8, FpbHLH11, FpbHLH13, FpbHLH14, FpbHLH15 ) showed down-regulated expression, while FpbHLH5, FpbHLH9 and FpbHLH10 were induced both in the compatible interaction and incompatible interaction. Furthermore, knockout of FpbHLH9 gene reduced the virulence in a susceptible wheat cultivar. Together, these results suggest that FpbHLHs may play different roles in virulence of F. pseudograminearum, and provide a good basis for further investigation.